Persepsi Pengunjung terhadap Keindahan Alam dan Daya Tarik Wisata Pantai Karang Tawulan sebagai Destinasi Unggulan di Kabupaten Tasikmalaya - Kurnia, Heri (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2025)
Karang Tawulan Beach in Cikalong District, Tasikmalaya Regency has significant potential as a leading tourist destination in West Java, but a comprehensive understanding of visitors' perceptions of natural beauty and tourist attractions is still limited. This study aims to explore and analyze visitors' perception of the natural beauty and tourist attractions of Karang Tawulan Beach as a leading destination in Tasikmalaya Regency, including identifying factors that affect visitor satisfaction and attractiveness. This research uses a qualitative approach with a narrative design, conducted through field research at Karang Tawulan Beach in the period from March to June 2025. Data were collected through in-depth interviews with 25 visitors, participatory observation and photographic documentation. Data analysis was carried out using thematic analysis to identify patterns and themes that emerged from visitor narratives. The findings of the study revealed that visitors perceive Karang Tawulan Beach to have extraordinary natural beauty, especially unique coral formations, clear blue sea water, and pristine white sand expanse. Visitors really appreciate the authenticity and natural atmosphere which has not been too touched by commercialization compared to other beaches that are more crowded. The main attraction factors include beautiful natural panoramas, photography spots, water sports activities, and a serene atmosphere. However, visitors also identified several aspects that need improvement, including limited infrastructure facilities, inadequate accessibility, limited parking areas and lack of information services. Visitor satisfaction is greatly influenced by the experience of natural beauty, cleanliness, safety, and quality of service. This study concludes that Karang Tawulan Beach has strong potential as a leading tourist destination, but requires integrated development that focuses on improving infrastructure while maintaining environmental sustainability and natural authenticity to improve visitor experience and destination competitiveness.